Updated Assessment of State Food Safety Laws for Norovirus Outbreak Prevention in the United States - Anita K. Kambhampati; E. Rickamer Hoover; Lisa A. Landsman; Beth C. Wittry; Laura G. Brown; Sara A. Mirza (Journal of Food Protection)
Foodborne norovirus outbreaks are often associated with food contamination during preparation by an ill employee. The US Food and Drug Administration’s Food Code outlines food safety provisions to prevent illness transmission in food establishments. An updated full version of the Food Code is released every four years; adoption of specific provisions is at the discretion of state governments.Food safety laws of the 50 states and District of Columbia (51 jurisdictions) were assessed for adoption as of March 2020, of four norovirus-related provisions included in the 2017 Food Code: (1) prohibition of barehand contact with ready-to-eat (RTE) food, (2) exclusion of food employees with vomiting or diarrhea, (3) person in charge being a certified food protection manager (CFPM), and (4) written response plan for vomiting or diarrheal events. We compared the frequency of adoption of the 2017 Food Code provisions to a previous assessment of adoption of these provisions in the 2013 Food Code.Prohibition of barehand contact with RTE food was adopted by 45 jurisdictions (88%), an increase from 39 jurisdictions (76%) in the previous analysis. Forty jurisdictions (78%) required exclusion of food employees with vomiting or diarrhea for ≥24 h after symptom cessation, an increase from 30 jurisdictions (59%). Provisions requiring the person in charge to be a CFPM and written response plan for contamination events were new to the 2017 Food Code; 5 jurisdictions (10%) required the person in charge to be a CFPM and 9 (18%) required a written response plan.Adoption of provisions prohibiting barehand contact with RTE food and requiring exclusion of ill food employees increased. Newer provisions, requiring a person in charge to be a CFPM and a written contamination response plan, were not as widely adopted. Increased adoption of Food Code provisions and improved compliance may decrease norovirus transmission in food establishments.